Pengaruh Intensitas Pengungkapan dalam Sustainability Report dan Return On Asset pada Return Saham - Nusantara, I Kadek Bayu Putra; Mertha, I Made (E-Jurnal Akuntansi; Vol 28 No 3 (2019)DO - 10.24843/EJA.2019.v28.i03.p19, 2019)
The research population is all companies listed on the Indonesia Stock Exchange (IDX) from 2014 to 2017 that issued sustainability reports. The sample is determined by purposive sampling technique with criteria that do not include financial companies and companies that publish sustainability reports for the 2014-2017 period in a row to obtain a sample of 15 companies. The analysis technique used is Multiple Linear Regression Analysis. The results of the analysis show that there is no influence between the relationship between the intensity of disclosure in the sustainability report on stock returns while. Tests on the second hypothesis get the result that there is an influence between the relationship of return on assets to the stock returns that the company will receive. Investors in investing in the capital market are expected to pay attention to conditions in the company such as ROA in order to get the desired stock return. Keywords : Sustainability report, asset returns, stock returns.